2021
DOI: 10.1002/aur.2479
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Temporal Discrimination in Autism Spectrum Disorder

Abstract: Sensory differences are common in Autism Spectrum Disorder (ASD). While there is no well‐accepted method to measure sensory differences objectively, there is accumulating evidence from recent years concerning sensory perception, including data concerning temporal discrimination thresholds of individuals with ASD as measured by different measures. The somatosensory temporal discrimination (STD) test measures the threshold at which an individual can temporally discriminate multiple tactile stimuli delivered in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…In the case of tactile perception, it has been shown that patients with ASD present a higher detection threshold for static stimuli (acute stimuli) and a lack of sensitivity to dynamic (which increases in amplitude over time to a detectable threshold) stimuli suggesting aberrant habituation, whereas healthy individuals show poorer detection of dynamic stimuli compared to static stimuli (Puts et al, 2014 ; Tavassoli et al, 2016 ). Additionally, the temporal discrimination of successive tactile stimulations seems also to be altered with an increased threshold of detection (Buyuktaskin et al, 2021 ). Moreover, patients with ASD have an aversion to touch, suggesting that a tactile stimulus, albeit weak, is a source of discomfort indicating a potential hypersensitivity to this type of stimulus (Moore, 2015 ; Kaiser et al, 2016 ).…”
Section: Part 2: Importance Of the Oxytocinergic System In The Sensor...mentioning
confidence: 99%
“…In the case of tactile perception, it has been shown that patients with ASD present a higher detection threshold for static stimuli (acute stimuli) and a lack of sensitivity to dynamic (which increases in amplitude over time to a detectable threshold) stimuli suggesting aberrant habituation, whereas healthy individuals show poorer detection of dynamic stimuli compared to static stimuli (Puts et al, 2014 ; Tavassoli et al, 2016 ). Additionally, the temporal discrimination of successive tactile stimulations seems also to be altered with an increased threshold of detection (Buyuktaskin et al, 2021 ). Moreover, patients with ASD have an aversion to touch, suggesting that a tactile stimulus, albeit weak, is a source of discomfort indicating a potential hypersensitivity to this type of stimulus (Moore, 2015 ; Kaiser et al, 2016 ).…”
Section: Part 2: Importance Of the Oxytocinergic System In The Sensor...mentioning
confidence: 99%
“…Sensory quadrants have been utilized (Marche et al, 2012 ; Takahashi et al, 2018 ; Uljarević et al, 2014 ) to describe four primary areas of poor registration, seeking, sensitivity, and avoidance. Factor scores have also been derived by Ermer & Dunn ( 1998 ) and are utilized to distinguish between neurotypical and clinical samples (Ben-Sasson et al, 2009 ; Buyuktaskin et al, 2021 ; Chistol et al, 2018 ; Loh et al, 2021 ; Tomchek et al, 2014 ). Lastly, items can be split by high- and low-threshold (Takahashi et al, 2018 ; Tzischinsky et al, 2018 ) to broadly explore thresholds by which sensory stimuli may elicit responses.…”
Section: Genetic Subgroups and Relevant Sensory Behaviorsmentioning
confidence: 99%
“…Evaluation of the tactile modality was based on detection thresholds. The three tasks identified are the somatosensory temporal detection thresholds (STDT, Buyuktaskin et al, 2021) and the 'touch-test sensory evaluators' and 'two-point discriminator task' (Demopoulos et al, 2015a).…”
Section: [Insert Here Table 1]mentioning
confidence: 99%